Chrysin as an Anti-Cancer Agent Exerts Selective Toxicity by Directly Inhibiting Mitochondrial Complex II and V in CLL B-lymphocytes. (16th March 2017) - Salimi, Ahmad; Roudkenar, Mehryar Habibi; Seydi, Enayatollah; Sadeghi, Leila; Mohseni, Alireza; Pirahmadi, Nahal; Pourahmad, Jalal
ABSTRACT: We investigated the effect of chrysin on isolated normal and chronic lymphocytic leukemia (CLL) B-lymphocytes and their isolated mitochondria. We report that a selective and significant increase in cytotoxicity, intracellular reactive oxygen species, mitochondrial membrane potential collapse, ADP/ATP ratio, caspase 3 activation and finally apoptosis in chrysin-treated CLL B- lymphocytes. Also we determined that chrysin selectively inhibits complex II and ATPases in cancerous mitochondria. In this study we proved that the ability of chrysin to promote apoptosis in CLL B-lymphocytes performed by selectively targeting of mitochondria. Our findings may provide a potential therapeutic approach for using chrysin to target mitochondria in CLL B-lymphocytes.